2019
DOI: 10.1177/1352458519845116
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the retinal vasculature occur in multiple sclerosis and exhibit novel correlations with disability and visual function measures

Abstract: Background: The retinal vasculature may be altered in multiple sclerosis (MS), potentially acting as a biomarker of disease processes. Objective: To compare retinal vascular plexus densities in people with MS (PwMS) and healthy controls (HCs), and examine correlations with visual function and global disability. Methods: In this cross-sectional study, 111 PwMS (201 eyes) and 50 HCs (97 eyes) underwent optical coherence tomography angiography (OCTA). Macular superficial vascular plexus (SVP) and deep vascular pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
97
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(115 citation statements)
references
References 39 publications
17
97
1
Order By: Relevance
“…More precisely, VD decrease remains significant when we remove outliers. Our results support previous research, such as Lanzillo R et al [12] (with Octovue OCTA device) and Olwen C Murphy et al [30] (Spectralis OCTA), both showing a loss of VD in SVP macular ETDRS in MS patients. Only one study evidenced an increase in VD in MS patients [31], which was realized with Angioplex Zeiss device.…”
Section: Discussionsupporting
confidence: 93%
“…More precisely, VD decrease remains significant when we remove outliers. Our results support previous research, such as Lanzillo R et al [12] (with Octovue OCTA device) and Olwen C Murphy et al [30] (Spectralis OCTA), both showing a loss of VD in SVP macular ETDRS in MS patients. Only one study evidenced an increase in VD in MS patients [31], which was realized with Angioplex Zeiss device.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, in recent reports, vessel density of the SCP and DCP showed variations in both directions (i.e., increased or decreased) ( Table 2 ) [ 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 ]. Some authors reported a decreased SCP in both patients with MSON and MSNON [ 92 , 95 , 97 , 98 ]. Conversely, Feucht et al found a decreased SCP and DCP only in eyes with a history of ON.…”
Section: Multiple Sclerosismentioning
confidence: 94%
“…Moreover, parafoveal vascular density was negatively correlated with the EDDS, which is one of the most common used score to assess disability due to MS [ 93 ]. According to these results, Murphy et al, showed that SVD was negatively correlated with both EDDS and multiple sclerosis functional composite scale [ 98 ]. These results highlight the role of retinal vascular density as a possible novel biomarker to monitor MS progression.…”
Section: Multiple Sclerosismentioning
confidence: 99%
“…OCTA may be implemented in several interesting ways to advance the understanding of neuroinflammatory disease. Studies investigating OCTA in neuroinflammatory disease found that its findings are usually highly correlated to measurements of retinal layer thickness performed with the more consolidated technique of OCT (20)(21)(22). Therefore, OCTA can be an alternative quantitative measure of damage to the retina and optic nerve, as atrophied tissue requires less blood supply (20).…”
Section: Introductionmentioning
confidence: 99%